Importance and Obstacles of First Aid in Burn Injuries; A Letter to The Editor - Madadizadeh, Farzan; Afzal, Golnaz (Archives of Academic Emergency Medicine, 2024)
After a burn injury, pre-hospital care, which includes first aid measures before transfer to a burns center, is considered to be a significantly important step in the process of burn treatment. Individuals who receive medical care at a hospital following initial first aid administered at home experience a better outcome. This letter aimed to discuss about the importance and obstacles of prehospital management of burn injuries.